Heavy Chalcogen Properties of Sulfur and Selenium Enhance Nucleic Acid-Based Therapeutics - Stephen J. Dansereau; Jia Sheng (Biomolecules, 2025)
The Group 16 elements of the periodic table have a characteristic valence shell configuration instrumental to their chemical properties and reactivities. The electrostatic potentials of these so-called chalcogens have been exploited in the design of materials that require the efficient passage of electrons including supermagnets, photocatalytic dyes, and solar panels. Likewise, the incorporation of the heavy chalcogen selenium into organic frameworks has been shown to increase the reactivities of double bonds and heterocyclic rings, while its interactions with aromatic side chains in the hydrophobic core of proteins via selenomethionine impart a stabilizing effect. Typically present in the active site, the hypervalence of selenocysteine enables it to further stabilize the folded protein and mediate electron transfer. Selenium’s native occurrence in bacterial tRNA maintains base pair fidelity, most notably during oxidative stress, through its electronic and steric effects. Such native modifications at the positions 2 and 5 of uridine render these sites relevant in the design of RNA-based therapeutics. Innocuous selenium substitution for oxygen in the former and the standard methods of selenium-derivatized oligonucleotide synthesis and detection have led to the establishment of a novel class of therapeutics. In this review, we summarize some progress in this area.